Desain Kawasan Wisata Pusat Kerajinan Perak Kabupaten Bantul - Juniarsih, Wigati Lulus; , Ir. Nurhasan, MT (2016)
ABSTRACT As a historical district, Kotagede is also well known as a producer of silver. Various traditions especially those owned by local residents Kotagede like a traditional home, traditional cuisine and indigenous livelihoods as silversmiths gradually reduced hard to find. From the above review authors interested in designing an area dedicated to the silversmith in Kampung Jagalan Kotagede, as a place to manufacture or workshops and points of sale. So that tourists can be easy to find original silver Kotagede, besides tourists can also learn in making the silver. The purpose of this study the authors make an area devoted to the Jagalan Kotagede silversmith village, to preserve the existence of such craft and create a tourist attraction for introducing tourists of silver in Jagalan village, district. Banguntapan, Kab. Bantul. The method employed by literature studies, observational studies, interviews, data analysis with descriptive method. Based on the analysis of the object, the location and footprint, and an analysis of the composition and architectural forms, as well as studies on the theme of Neo Vernakuler schools of architecture, it can be concluded some design criteria that will be used in the process of transformation of the concept with the aim of maximizing yield. Kata Kunci : Kabupaten Bantul, Kerajinan Perak, wisata.